Impact of global value chains on performance of small and medium-sized enterprises in Sri Lanka: Evidence from Sri Lanka - N. P. Ravindra Deyshappriya; B.C.H. Maduwanthi (Asian Development Bank Institute (ADBI), 2020)
The current study examines the impact of GVCs on the performance of SMEs in Uva and central provinces of Sri Lanka while recognizing potential local business sectors that can be linked with GVCs. Apart from that, key challenges and main success factors in relation to linking SMEs with GVCs are also identified. A total of 329 SMEs in both provinces were surveyed to collect quantitative data while four and eight FGDs and KIIs, respectively, were conducted to gather qualitative information. Both econometric and descriptive analyses were employed to accomplish the objectives of the research. The econometric analysis found that SMEs that are linked with GVCs have a higher level of profit than those that are not. Apart from the direct impact of GVCs, the study also observed that linking with GVCs indirectly increases the performance of SMEs through enhancing the sales revenue and research and development activities of SMEs. The descriptive analysis recognized five main business sectors, namely information technology, apparel, gems and minerals, tea and other agricultural products, and handcraft, as the sectors with the most potential to link with GVCs. Among these five sectors, SMEs in information technology, apparel, and gems and minerals are more likely to link with GVCs. In addition, the study recognized challenges such as a lack of access to finance, a lack of technology, a lack of information, being unable to meet quality standards, and an inability to produce the quantity required as the main obstacles to linking with GVCs. Furthermore, factors such as ensuring the quality of products, the availability of skilled labor, better access to finance, access to better technologies, the ability to produce at low cost, and access to BDSs increase the potential to link SMEs with GVCs. The findings of the study strongly recommend that government, nongovernment organizations, and policy makers should encourage SMEs to participate in GVCs by allowing them to grow as internationally competitive entrepreneurs.
Keywords: B17; O24; M11; Q01; 330; global value chain; small and medium-sized enterprises; production networks; sustainable SME development